Bone marrow biopsy in non-Hodgkin lymphoma: A morphological study - Kumar Suneet; Rau Aarathi; Naik Ramadas; Kini Hema; Mathai Alka; Pai Muktha; Khadilkar Urmila (Wolters Kluwer Medknow Publications, 2009)
Context: Bone marrow (BM) biopsy is an integral part of staging work-up for non-Hodgkin lymphoma (NHL). Aims: To study the characteristics of BM involvement in NHL with respect to incidence, histologic pattern and morphology of infiltration and its discordance with the histology of primary anatomic site. Settings and Design: Forty-nine cases of NHL in which BM biopsy was performed for staging were included in this study, the primary site being classified according to the WHO classification for NHL. Materials and Methods: A prospective study of 49 cases was conducted. Bilateral BM biopsy was obtained from the posterior superior iliac spine. The biopsies were fixed in 10% buffered formalin solution and decalcified using 10% formal - formic acid for 4 - 6 h followed by routine processing. The serial sections were stained by hematoxylin and eosin and reticulin stains. Results: BM biopsy showed involvement by lymphoma in 27 cases (55.10%). Unilateral positivity was found in four cases (14.81% cases). The overall incidence of marrow involvement by NHL was 55.1%. The incidence of involvement was higher in T-cell lymphomas when compared with B-cell lymphomas and predominant pattern of involvement was mixed. Diffuse large B-cell lymphomas had the lowest incidence in all the B-cell lymphomas. A discordant histology between BM and primary anatomic site was found in 29.63% (8/27) of the cases, where it was seen more in follicular lymphomas and diffuse large B-cell lymphomas. Conclusions: Critical examination of BM biopsies can increase the diagnostic accuracy, thereby contributing to the prognosis and appropriate treatment modalities.